Moral Values ​​in Classical Folklore Literature "The Legend of Curug Orok" in Cikandang Village, Cikajang District, Garut Regency as an Effort to Preserve Cultural Values - Iin Indriyani; Umi Kulsum (Journal Civics And Social Studies, 2021)
Fairy tales are one of the cultural products originating from Indonesian society. The existence of fairy tales itself today is almost extinct, eroded by the sophistication of communication technology, and many young people today do not even know that in the area where they live, there are stories stored. In fact, if we dig into the contents of the messages in these fairy tales, there are many moral values ​​that can be used as guidance for living life. Moral values ​​are values ​​that regulate the way of life when we are in a social environment. The aim of this research is to analyze the moral values ​​in the folklore entitled "Legend of Curug Orok". This fairy tale comes from Cikandang Village, Cikajang District, Garut Regency. The research method used is descriptive analysis. The results of the researcher's analysis of the moral values ​​contained in the folklore entitled "Legend of Curug Orok" are honesty, responsibility, independence, moral courage and humility. It is hoped that the results of this research will increase insight into the wider community regarding the richness of Indonesian culture in the form of folk tales originating from areas in Garut Regency, as well as an effort to preserve them, so that the existence of these folk tales does not become extinct just .